L'allocation des credits de recherche sur l'elevage en Afrique au sud du Sahara - McIntire, John M. (1985)
Describes possible methods of allocating research resources based on different analytical models. Presents a brief review of models proposed; and some evidence about current agricultural and livestock reserch in sub-Saharan Africa. Also presents emperical tests of which variables might be important in defining the research priorities in 32 of ILCA's mandate countries. Compares ILCA's current allocation of funds and those suggested by the models.